1/(x + y) + 1/(x - y) = 6 (1)
6/(x + y) - 1/(x - y) = 1 (2)
x ≠ y
x ≠ -y
складываем (1) и (2)
1/(x + y) + 1/(x - y) + 6/(x + y) - 1/(x - y) = 6 + 1
7/(x + y) = 7
x + y = 1
умножаем (1) на 6 и вычитаем (2)
6/(x + y) + 6/(x - y) = 36
6/(x + y) + 6/(x - y) - (6/(x + y) - 1/(x - y)) = 36 - 1
7/(x - y) = 35
x - y = 1/5
получили новую систему
2х = 6/5
x = 3/5
2y = 4/5
y = 2/5
ответ {3/5 2/5}
1/(x + y) + 1/(x - y) = 6 (1)
6/(x + y) - 1/(x - y) = 1 (2)
x ≠ y
x ≠ -y
складываем (1) и (2)
1/(x + y) + 1/(x - y) + 6/(x + y) - 1/(x - y) = 6 + 1
7/(x + y) = 7
x + y = 1
умножаем (1) на 6 и вычитаем (2)
6/(x + y) + 6/(x - y) = 36
6/(x + y) + 6/(x - y) - (6/(x + y) - 1/(x - y)) = 36 - 1
7/(x - y) = 35
x - y = 1/5
получили новую систему
x + y = 1
x - y = 1/5
2х = 6/5
x = 3/5
2y = 4/5
y = 2/5
ответ {3/5 2/5}